The Dead Sea scrolls in scholarly perspective : a history of its research - Dimant, Devorah.; Kottsieper, Ingo. (Studies on the Texts of the Desert of Judah, 2012)
The volume consists of 27 surveys of research into the Dead Sea Scrolls in the past 60 years, written by 26 authors. An innovation of the volume is that it covers Qumran scholarship in separate countries: the USA, Canada, Israel, France, Germany, Spain, the Netherlands, Scandinavia, Italy and the Eastern bloc. Each essay also carries a detailed bibliography for the respective country. Biographies of all the major scholars active in the field are briefly given as well. This book thereby exhaustively surveys past and present Qumran research, outlining its particular development in various circumstances and national contexts. For the first time, perspectives and information not recorded in any other publication are highlighted.